2010
DOI: 10.1038/oby.2009.255
|View full text |Cite
|
Sign up to set email alerts
|

Parametrial Adipose Tissue and Metabolic Dysfunctions Induced by Fructose‐rich Diet in Normal and Neonatal‐androgenized Adult Female Rats

Abstract: Hyperandrogenemia predisposes an organism toward developing impaired insulin sensitivity. The aim of our study was to evaluate endocrine and metabolic effects during early allostasis induced by a fructose-rich diet (FRD) in normal (control; CT) and neonatal-androgenized (testosterone propionate; TP) female adult rats. CT and TP rats were fed either a normal diet (ND) or an FRD for 3 weeks immediately before the day of study, which was at age 100 days. Energy intake, body weight (BW), parametrial (PM) fat chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(84 citation statements)
references
References 42 publications
3
76
0
5
Order By: Relevance
“…obesity; litter size; leptin; fat mass NUMEROUS STUDIES HAVE SHOWN that an individual's propensity to gain weight during adulthood can be affected by prenatal and neonatal changes in nutrition (23,42,57). Moreover, it is now clear that it is not only the amount but also the type of energy consumed that determines weight gain and body composition during both early development and adulthood (1,23,40,54). Thus, poor nutrition and overnutrition during maturational periods and adulthood are likely to synergize in causation of the exponential rise in obesity observed in many populations.…”
mentioning
confidence: 97%
“…obesity; litter size; leptin; fat mass NUMEROUS STUDIES HAVE SHOWN that an individual's propensity to gain weight during adulthood can be affected by prenatal and neonatal changes in nutrition (23,42,57). Moreover, it is now clear that it is not only the amount but also the type of energy consumed that determines weight gain and body composition during both early development and adulthood (1,23,40,54). Thus, poor nutrition and overnutrition during maturational periods and adulthood are likely to synergize in causation of the exponential rise in obesity observed in many populations.…”
mentioning
confidence: 97%
“…the unhealthy expansion) of its cells [6] and an increased peripheral/VAT oxidative stress [3]. However, the underlying mechanism whereby the FRD induces this selective adipocyte hypertrophy rather than its hyperplasia remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the low leptin levels found in FTM rats, it has been reported that in the adult neonatally androgenized female rat [48] and in the normal male rat over-development [49] , the increase in plasma leptin levels seems to be related, at least in part, to an androgen effect. It has been claimed that there is a proinflammatory role of leptin [23] , which could contradict our data on LPS-stimulated TNF ␣ secretion in FTM rats.…”
Section: Discussionmentioning
confidence: 99%